QT DURATION AND DISPERSION IN ANGINA AND MYOCARDIAL INFARCTION - O. K. Rybak; P. Y. Dovgalevsky; N. V. Furman; M. R. Shamyunov; A. P. Averyanova; I. A. Morozov (Российский кардиологический журнал, 2001)
We have studied 176 men, including 84 with acute myocardial infarction (mean age 59,2±2,2), 92 (mean age 49,2±3,5) with angina of various functional classes. We have registered 12-lead ECG at rest (50 mm/sec) to all simultaneously. QT and QTc dispersion were calculated as the difference between their maximal and minimal durations in all the 12 leads. The prognostic role of QT dispersion as a marker of potentially life-threatening arrhythmias, is insufficient in the angina group. Unlike those, patient with acute myocardial infarction demonstrate a far greater role QT time parameters in predicting potentially life-threatening arrhythmias; with QT dispersion sensitivity and specificity (threshold > 50 msec) proved 82,2% and 85,8% respectively, and for QTc (threshold ≥ 70 msec) – 88,1% and 94,5%.